The Role of Popular Culture in Rural-to-Urban Transformation Contributing to the “Slušovice Miracle” - Fialka, Jiří (Lidé města, 2017)
The submitted article provides inquiry into the role of popular culture in the everyday life of Slušovice – the socialist “center municipality” and extraordinary isle of prosperity in the scarce economy of Czechoslovakia in the 1970s and 1980s. It presents research on the popular culture of the formative political environment of state socialism. The urbanisation and suppression of traditional culture in this village was not isolated from the broader context, but was derived from the economic transformation of the local collective farm and its symbolic differentiation from socialism. In these intentions, the study tries to expand the specific dimensions of the emergent popular culture with its emphasis on huge cultural events, showing the hybridity of social life in Slušovice, which was created by the combination of rural transformation and consumer culture.